The geological history of the Latimojong region of western Sulawesi, Indonesia. (1st May 2017) - White, Lloyd T.; Hall, Robert; Armstrong, Richard A.; Barber, Anthony J.; BouDagher Fadel, Marcelle; Baxter, Alan; Wakita, Koji; Manning, Christina; Soesilo, Joko
Graphical abstract: Highlights: We review the stratigraphy and tectonic history of the Latimojong Mountains region. We found that the Latimojong Formation does not occur in this region. We present new fossil ages for the Toraja Fm., Makale Fm. And Enrekang Volcanics. We present new U-Pb zircon SHRIMP data for igneous rocks in the region. The region is dominated by strike-slip faulting. Abstract: We present an updated geological map and revised stratigraphy of the Latimojong region of central–western Sulawesi. This work includes new biostratigraphic ages from the Latimojong Metamorphic Complex, Toraja Group, Makale Formation and Enrekang Volcanics, together with whole-rock geochemical data and sensitive high-resolution ion microprobe (SHRIMP) U-Pb analyses from zircons extracted from igneous rocks in the region. Previous work on the study region and in other parts of Sulawesi have discussed the age and character of two different rock sequences with similar names, the Latimojong Complex and the Latimojong Formation. One would assume that the type location for these two sequences is in the Latimojong Mountains. However, there is considerable confusion as to the character and location of these sequences. We make a distinction between the Latimojong Formation and the Latimojong Complex, and propose that the Latimojong Complex be renamed the Latimojong Metamorphic Complex to minimise the confusion associated with the current nomenclature. The Latimojong Metamorphic Complex is an accretionary complex of low- to high-grade metamorphic rocks tectonically mixed with cherts and ophiolitic rocks, while the Latimojong Formation consists of Upper Cretaceous weakly deformed, unmetamorphosed sediments or very low-grade metasediments (previously interpreted as flysch or distal turbidites that unconformably overlie older rocks). Our work indicates that the Latimojong Formation must be restricted to isolated, unobserved segments of the Latimojong Mountains, or is otherwise not present in the Latimojong region, meaning the Latimojong Formation would only be found further north in western Sulawesi. Radiolaria extracted from chert samples indicate that the Latimojong Metamorphic Complex was likely assembled during the Cretaceous (Aptian-Albian) and was later metamorphosed. Ages obtained from benthic and planktonic foraminifera were used to differentiate and map the Toraja Group (Ypresian to Chattian: 56–23 Ma), Makale Formation (Burdigalian to Serravallian: 20.5–11.5 Ma) and Enrekang Volcanic Series (8.0–3.6 Ma) across the study area. U-Pb isotopic data collected from magmatic zircons record several phases of volcanism (∼38 Ma, ∼25 Ma and 8.0–3.6 Ma) in the region. Each phase of magmatism can be distinguished according to petrology and whole-rock geochemical data. The isotopic ages also show that dacites from the Enrekang Volcanic Series are contemporaneous with the emplacement of the Palopo Granite (6.6–4.9 Ma). Miocene to Proterozoic inherited zircons within these igneous rocks support earlier suggestions that Sulawesi potentially has a Proterozoic–Phanerozoic basement or includes sedimentary rocks (and therefore detrital zircons) derived from the erosion of Proterozoic or younger material. Some earlier work proposed that the granitic rocks in the region developed due to crustal melting associated with plate collision and radiogenic heating. Our observations however, support different interpretations, where the granites are associated with arc magmatism and/or crustal extension. The region was cross-cut by major strike-slip fault zones during the Pliocene. This deformation and the buoyancy associated with relatively young intrusions may have facilitated uplift of the mountains.